Biomedical Waste Management among Primary Health Care Workers, Bauchi Local Government Area, Bauchi State, NIGERIA - Yusuf Sarkingobir; Asiya Gidado Yabo; Safina Abdullahi Yarima; Yusuf Yahaya Miya; Ibrahin Friday Sule; Nabil Riskuwa Bello; Abubakar Shehu (Jurusan Teknik Elektromedik, POLTEKKES KEMENKES Surabaya, Indonesia, 2022)
Biomedical waste management is a serious issue to health and environment that must be addressed at primary health care level, especially in Bauchi local government area of Bauchi state. The objectives of this study were to assess on the knowledge, methods and problems of biomedical waste management among the primary health care workers in some selected Health Care Centers of Bauchi L.G.A. of Bauchi state. A cross sectional study was employed and sampling techniques were used to distribute a questionnaire and interview among the health workers at twenty (20) selected primary health centers with (200) sample respondents from public and private health care centers. The result from the current study shows that the knowledge of biomedical waste management awareness among the workers was represented (94%), and only (6%) were not aware. The majority of PHC workers practiced open dumping and burning method (74%), incineration (7%), chemical treatment and only 1% for autoclave methods. while, microwaving (0%), encapsulation (0%) and sanitary landfill methods (0%) were not practiced. The problems of biomedical waste management included improper planning (33%), insufficient funds (25%), lack of material (19%) and (15%) lack of staffs training. There was improper segregation, lack of planning, lack of funds and practiced open dumping and burning, which is against the biomedical Waste (Management and Handling) Rules of 2016. There was improper biomedical waste management at primary health care level in Bauchi local government of Bauchi state. Thus, the Bauchi government should give more consideration towards good plan, allocation resources, set a committee of adequate supervision, monitoring and evaluation for the sustainable biomedical waste management at Bauchi local government of Bauchi state. .